77 Clinical Predictors of Local and Atypical Site Recurrence After Partial and Radical Nephrectomy for Localized Renal Cell Carcinoma - Andrea Lopez Sanmiguel; Rebecca Sager; Rebecca Yu; Melissa Assel; Nicole Liso; Daniel Barbakoff; Yash Khandwala; Judith Murciano; Karim Toujier; Jonathan Coleman; Andrew Vickers; A Ari Hakimi; et al. (The Oncologist, 2026)
Abstract Background Local recurrence (LR) after nephrectomy for localized renal cell carcinoma (RCC) is rare but associated with poor oncologic outcomes. Definitions of LR remain inconsistent across studies, and atypical recurrences involving non-traditional intra-abdominal and incisional sites are poorly characterized. Emerging evidence suggests that minimally invasive surgical techniques may influence LR patterns. Here, we evaluate predictors and patterns of LR, with a specific focus on atypical presentations. Methods Using a prospectively maintained institutional kidney surgery database, we identified patients with localized RCC who underwent nephrectomy between 2000 and 2024 and had at least one post-operative cross-sectional imaging study. LR was defined as a new lesion on follow-up imaging and was classified according to criteria developed by Lee et al. This system defines the following: Type I, a single recurrence in the remnant kidney or ipsilateral renal fossa; Type II, a single recurrence involving the ipsilateral vasculature, ipsilateral adrenal, or regional lymph nodes; Type II, a single recurrence in other intra-abdominal soft tissues or organs; and Type IV, any combination of Types I-III or multiple of a single type. Predictors of LR-free survival were evaluated using multivariable Fine-Gray competing risks regression, with metastasis or death as competing events. We assessed predictors of any atypical (Type III or Type IV including Type III) recurrence using univariable Fine-Gray models. Secondary interaction analyses were performed to test whether the association between predictors and any atypical recurrence differed by surgical approach (open vs minimally invasive). Results Among 3,815 patients with localized RCC who underwent nephrectomy, 122 developed a LR, including 37 patients with an atypical (Type III) recurrence. At 20 years, cumulative incidence was 8.6% for any LR and 16% for metastasis; any Type III recurrence was rare at 2.5%. Positive surgical margins specifically in minimally invasive surgery were strongly associated with increased risk of LR (SHR 6.05; 95% CI 2.84, 12.9) and any Type III recurrence (SHR 9.03; 95% CI 3.20, 25.5). Other predictors included higher tumor stage, high grade, and partial nephrectomy. Conclusions LR after nephrectomy was uncommon, including atypical presentations, which rarely occurred before other competing events. Overall, predictors of LR were similar for minimally invasive and open approaches; however, positive surgical margins were strongly associated with overall and atypical LR specifically after minimally invasive surgery. Higher stage and grade were independently associated with increased LR risk. These findings highlight the predominant role of tumor biology in determining recurrence risk. Furthermore, surgeons should make every effort to avoid positive surgical margins during nephrectomy by any technique.